2003
DOI: 10.1021/ma0257189
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Properties of Anchored Polymers with a Gradual Variation of Grafting Densities on Flat Substrates

Abstract: We show that assemblies comprising anchored polymers with a gradual variation of grafting densities on solid substrates can be generated by first covering the substrate with a molecular gradient of the polymerization initiator, followed by polymerization from the substrate-bound initiator centers (“grafting from”). We apply this technique to prepare grafting density gradients of poly(acrylamide) (PAAm) on flat silica substrates. We demonstrate that using the grafting density gradient geometry, the mushroom-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
228
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(239 citation statements)
references
References 28 publications
11
228
0
Order By: Relevance
“…75 Genzer et al studied graft-density effects using a gradient approach in poly(acrylamide) (PAA), and found that in the brush regime the thickness scaled as ρ 1 / 3 g , suggesting all chains along the gradient were the same size. 77 Fukuda et al, however, reported that the brush height in a PMMA system from silica wafers at moderate graft density obeyed the ρ 1 / 3 g law, but at high graft density (ρ g > 0.7 chains nm 2 ) approached ρ 1 / 2 g ; again direct molecular weight measurements of the brush layer were not conducted and so here the possibility of a R p dependence on ρ g cannot be discounted. 85 In this publication we report a strong dependence of R p on ρ g in SI-ATRP of polystyrene (PS) from MMT.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…75 Genzer et al studied graft-density effects using a gradient approach in poly(acrylamide) (PAA), and found that in the brush regime the thickness scaled as ρ 1 / 3 g , suggesting all chains along the gradient were the same size. 77 Fukuda et al, however, reported that the brush height in a PMMA system from silica wafers at moderate graft density obeyed the ρ 1 / 3 g law, but at high graft density (ρ g > 0.7 chains nm 2 ) approached ρ 1 / 2 g ; again direct molecular weight measurements of the brush layer were not conducted and so here the possibility of a R p dependence on ρ g cannot be discounted. 85 In this publication we report a strong dependence of R p on ρ g in SI-ATRP of polystyrene (PS) from MMT.…”
Section: Introductionmentioning
confidence: 82%
“…69,70 In more recent years researchers have realized the potential for utilizing ATRP to modify the surface chemistry of many materials. Colloidal silica, 71 montmorillonite clay (MMT), 72 gold films, [73][74][75] [76][77][78] have been the most frequently studied substrates for surface initiated (SI)-ATRP, where the first is a spherical particle and the last three are high aspect ratio materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the measured brush height in this regime is h ≈ 2R g . 4 Only when these "mushrooms" begin to overlap do the chains begin to behave as brushes.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In more recent years, researchers have realized the potential for utilizing ATRP to modify the surface chemistry of many materials. Colloidal silica, 4 montmorillonite clay (MMT), 5 gold films, [6][7][8] and silicon wafers [9][10][11] have been the most frequently studied substrates for surface-initiated (SI)-ATRP, where the first is a spherical particle and the last three are high-aspect-ratio materials.…”
Section: Introductionmentioning
confidence: 99%